"You should go so that others can come"; the role of facilities in determining an early departure after childbirth in Morogoro Region, Tanzania. Issue 1 (December 2015) - McMahon, Shannon; Mohan, Diwakar; LeFevre, Amnesty; Mosha, Idda; Mpembeni, Rose; Chase, Rachel; Baqui, Abdullah; Winch, Peter
Abstract Background Tanzania is among ten countries that account for a majority of the world's newborn deaths. However, data on time-to-discharge after facility delivery, receipt of postpartum messaging by time to discharge and women's experiences in the time preceding discharge from a facility after childbirth are limited. Methods Household survey of 1267 women who delivered in the preceding 2–14 months; in-depth interviews with 24 women, 12 husbands, and 5 community elders. Results Two-thirds of women with vaginal, uncomplicated births departed within 12 h; 90 % within 24 h, and 95 % within 48 h. Median departure times varied significantly across facilities (hospital: 23 h, health center: 10 h, dispensary: 7 h, p < 0.001). Quantitative and qualitative data highlight the importance of type of facility and facility amenities in determining time-to-discharge. In multiple logistic regression, level of facility (hospital, health center, dispensary) was the only significant predictor of early discharge (p = 0.001). However across all types of facilities a majority of women depart before 24 h ranging from hospitals (54 %) to health centers (64 %) to dispensaries (74 %). Most women who experienced a delivery complication (56 %), gave birth by caesarean section (90 %), or gave birth to a pre-term baby (70 %) stayed longer than 24 h. Reasons for early discharge include: facility practices including discharge routines and working hours and facility-based discomforts for women and those who accompany them to facilities. Provision of postpartum counseling was inadequate regardless of time to discharge and regardless of type of facility where delivery occurred. Conclusion Our quantitative and qualitative findings indicate that the level of facility care and comforts existing or lacking in a facility have the greatest effect on time to discharge. This suggests that individual or interpersonal characteristics play a limited role in deciding whether a woman would stay for shorter or longer periods. Implementation of a policy of longer stay must incorporate enhanced postpartum counseling and should be sensitive to women's perceptions that it is safe and beneficial to leave hospitals soon after birth.